The Past, Present, and Future of Adoptive T Cell Therapy - Choi, Donghoon (The Korean Association of Immunologists, 2012)
Although adoptive T cell therapy (ACT) has become a promising immunotherapeutic regime for cancer treatment, its effectiveness has been hindered by several inherent shortcomings regarding safety and efficacy. During the past few decades, several strategies for enhancing the efficacy of ACT have been developed and introduced in clinic. This review will summarize not only the past approaches but also the latest strategies which have been shown to enhance the anticancer activity of ACT.